Respostas a ambientes institucionais policêntricos: hierarquização de recursos para o desenvolvimento de práticas de responsabilidade social corporativa - Anjos, Silvina Maria dos (2024)
This thesis aims to explain how firms respond to normative polycentric institutional pressures by developing and reconfiguring their resources and capabilities to implement Corporate Social Responsibility (CSR) practices. Although previous studies suggest a positive relationship between the implementation of CSR practices and firms' financial performance, there are still significant gaps in the academic literature that deserve attention, with three key gaps in this thesis. The first gap concerns how firms respond to polycentric institutions in volatile and uncertain contexts, especially in structuring normative responses. Second, there is a scarcity of empirical studies that explore firms' behavior in implementing sustainable practices in the firm, such as the use of administrative processes, regulations, and tools. Third, studies are limited in developed countries and scarce in emerging economies, where structural and institutional challenges are more pronounced. Given this, this study seeks to answer how companies build resources and capabilities to implement CSR over time to respond to normative polycentric institutional pressures? The theoretical lens chosen was the Resource-Based Theory (RBT) to answer the research question due to its ability to explain how an organization's unique resources and capabilities can be mobilized to generate sustainable competitive advantages. RBT offers a robust framework for analyzing how value creation can be maximized in strategic contexts, especially when integrating heterogeneous resources that are valuable, rare, inimitable, and efficiently organized, which aligns with the challenges and objectives of CSR in the business scenario. The study was conducted based on qualitative-descriptive and procedural research through documentary analysis from a historical perspective (covering the period from 2005 to 2023). The research involved semi-structured interviews with 17 employees of an agribusiness company and three of its partners, as well as 50 archival data, which made it possible to highlight the critical events that influenced the implementation of CSR practices. Based on the empirical study, it was observed that the adoption of CSR practices was accelerated by the need for legitimacy and by pressure from multiple power centers. The study suggests that normative polycentric institutional pressures require innovative practices and highlights the relevance of CSR for business competitiveness. The results tend to be relevant with managerial implications, as they show that the normative polycentric pressures to which companies are susceptible lead them to distribute these pressures throughout the entire value chain, influencing both their suppliers and partners to mitigate the impacts and ensure a more efficient and adaptive response to the demands and challenges of the different centers of power and influence. The findings indicate that the company implemented robust CSR practices in response to polycentric institutional environments and developed internal resources and capabilities to meet social, environmental, and governance demands, which led to significant advances in accessing global markets sustainably.